ANALISIS PENGGAMBARAN FILMIS SKENARIO FILM BERTEMA SUPERNATURAL - FRANSISKUS XAVERIUS YATNO KARYADI (Institut Seni Indonesia Padangpanjang, 2022)
This research is aimed at obtaining comparisons of supernatural themes for screenwriters and for similar research. The research subject is the way of describing ideas about supernatural themes developed in West Sumatra which have been translated into film scenarios. The context is how a scriptwriter describes filmically through writing film scenes in a screenplay. Also, how a screenwriter relates the idea of describing the theme with the myths or conditions that develop in society.The data were collected through observation techniques and review of the screenplay script. Observations were made by reading supernatural-themed scenarios in order to obtain a general narrative description, making the essence of the story in the form of a synopsis, and carrying out analysis. The method of analysis was that the scenario was summarized into a synopsis; the screenplay describes the filmic depiction of the scenes; the level of clarity of the filmic depiction was categorized; and an analysis of the sequence of clarity was made. The analytical approach used was a qualitative approach.The conclusion is that the characters created are generally supernatural beings that have strength, supernatural powers, telepathy, hurt or heal ability, and other manipulative things such as communicating with other worlds or having super powers. The story setting takes place in a place that is not like our world, or also like our world as the setting but beyond our understanding, by revealing something that our world does not have. Plot events cannot be explained by science, such as the greatness of the characters in using strength and supernatural powers. Stories tend to be full of strange occurrences in the form of unreasonable things throughout the story, with the appearance or presence of supernatural beings. The storyline depicts good versus evil, fighting demons, spirits and ghosts.